2020
DOI: 10.1002/smtd.202000314
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Functional Properties of Ti3C2Tx MXenes as Negative Electrodes in Sodium‐Ion Batteries by Chemical Tuning

Abstract: The large implementation of electrochemical energy storage devices requires the development of new chemistries tailored for specific uses. Sodium‐ion batteries (SIBs) can cover different application fields, however the state‐of‐the‐art negative material, hard carbon, suffers from poor cyclability and rate capability. MXenes are a vast class of 2D‐materials of the general formula Mn+1XnTx (M = transition metal, X = C or N, and T = M‐terminating group) with peculiar structural features able to reversible interca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 62 publications
11
42
0
Order By: Relevance
“…Here, the MXene layer plays an important role in the enhancement of kinetics due to its intrinsically high Na + diffusion coefficient (>3.0 × 10 −12 cm 2 S −1 ). [ 130 ] Furthermore, the improvement in ionic intercalation kinetics is even noticeable in multivalent‐ion batteries. DFT calculation shows the Mg 2+ diffusion barrier in MoS 2 /graphene heterostructures is 0.4 eV lower than that in MoS 2 bilayers (1.1 eV).…”
Section: The Roles Of Heterostructures In Rechargeable Batteriesmentioning
confidence: 99%
“…Here, the MXene layer plays an important role in the enhancement of kinetics due to its intrinsically high Na + diffusion coefficient (>3.0 × 10 −12 cm 2 S −1 ). [ 130 ] Furthermore, the improvement in ionic intercalation kinetics is even noticeable in multivalent‐ion batteries. DFT calculation shows the Mg 2+ diffusion barrier in MoS 2 /graphene heterostructures is 0.4 eV lower than that in MoS 2 bilayers (1.1 eV).…”
Section: The Roles Of Heterostructures In Rechargeable Batteriesmentioning
confidence: 99%
“…The synthesis of the Ti 3 AlC 2 MAX phase was done via spark plasma sintering and has been described in previous work. 53 In a typical synthesis, Ti/Al/TiC powders were mixed in an atomic ratio of 1/1/1.9 in a Turbula shaker (3D mixer TURBULA) for 24 h. The powders were rapidly heated to 1300 °C and pressed at 43 MPa between the pistons of the SPS for 5 min at an argon partial pressure of 300 mbar. The MAX phase disc produced was ground and sieved to obtain particles with a size below 50 μm.…”
Section: Methodsmentioning
confidence: 99%
“…52 Gentile et al showed different preparation routes of MXenes resulting in different structures, compositions, properties, and morphologies and investigated their influence on the application of NIBs. 53 The optimized Ti 3 C 2 T z shows a capacity of 110 mA h g −1 at a specific current of 0.03 A g −1 .…”
Section: Introductionmentioning
confidence: 95%
“…Due to the peculiar synthesis, the MXene maintains the same MAX phase lamellar nature, with each lamella made by a repetition of [T x (M n + 1 X n )T x ] k stacks. [14] As described above, the interlayers' interactions (dipolar and Van der Waals) related to the presence of terminal groups lead to formation of aggregated 2D bulk particles. [8] However, depending on the nature and stoichiometry of the T groups, this situation can be modulated and the weakness of the T•••T interlayers' interactions leads to the formation of larger and accessible interlayer spaces.…”
Section: Introductionmentioning
confidence: 94%
“…Despite the modest specific capacity, ranging from 110 to 150 mAh g À 1 in massive electrodes, the Ti 3 C 2 T x phase can be used for hundreds of cycles with very high Coulomb efficiency (> 99.5 % at low current) and 100 % capacity retention. [14] Given these interesting results as well as the great variety of applications of the Ti 3 C 2 T x phase, it is therefore important to make the production process simple, scalable, and globally more sustainable. The synthesis of these 2D materials, indeed, remains the bottleneck for the large production and application of the MXenes in different fields, due to the use of hydrofluoric acid, which is toxic, difficult to handle, and requires dedicated apparatus and facilities.…”
Section: Introductionmentioning
confidence: 99%